2019
DOI: 10.1186/s12885-019-5879-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of adjuvant radiotherapy after total hysterectomy in patients with uterine leiomyosarcoma or carcinosarcoma: a SEER-based study

Abstract: Background The clinical impact of adjuvant radiotherapy on uterine sarcoma is unclear, and may depend on the histological type. Hence, the aim of this study was to evaluate clinical outcomes of adjuvant radiotherapy after total hysterectomy in patients with leiomyosarcoma or carcinosarcoma. Methods Data were obtained from the Surveillance, Epidemiology, and End Results (SEER) program. Cox proportional hazards regression analyses were performed to identify risk factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 34 publications
0
34
0
2
Order By: Relevance
“…In their report from the SEER database (time period 2004-2013, FIGO stages I-III), Li et al found in their matched cohort analysis significant and clinically relevant effects of EBRT, of VBT and of their combination on overall survival, with hazard ratios of 0.65 and 0.62 for the single radiotherapy modalities and 0.47 for the combination [15]. Specific data for individual FIGO stages were not presented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their report from the SEER database (time period 2004-2013, FIGO stages I-III), Li et al found in their matched cohort analysis significant and clinically relevant effects of EBRT, of VBT and of their combination on overall survival, with hazard ratios of 0.65 and 0.62 for the single radiotherapy modalities and 0.47 for the combination [15]. Specific data for individual FIGO stages were not presented.…”
Section: Discussionmentioning
confidence: 99%
“…A significant impact of EBRT on overall survival becomes more prominent in the studies of patient groups including FIGO stages higher than I. Although these mostly do not contain stage-by-stage analyses, pronounced benefits, especially of the combination of EBRT and VBT, have been seen in the stage groups I-III by Li et al, with a hazard ratio of 0.47 [15], and by Stokes et al, with a hazard ratio of 0.74 [19], with both effects being stronger than those of EBRT of VBT alone in these studies, suggesting that patients at stage II or III benefit from radiotherapy consisting of more than VBT alone, possibly the combination of EBRT and VBT.…”
Section: Discussionmentioning
confidence: 99%
“…23 There is increasing role of adjuvant chemo-radiation now with signi cant overall survival however multiple demographic and clinical factors in uence the choice of adjuvant therapy. 24,25 Despite the use of aggressive therapy, only modest improvement in overall survival is noted over the last few decades with a ve-year overall survival rate of approximately 20-30%. 26 The occurrence of rare tumors like sporadic RH and MMT in the same patient is very rare entity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the GOG 161 study, ifosfamide/paclitaxel is considered the treatment of choice [21] and paclitaxel/ carboplatin is equally effective [22] as adjuvant treatment and was used by our medical oncology team [23]. There is increasing role of adjuvant chemo-radiation now with significant overall survival; however, multiple demographic and clinical factors influence the choice of adjuvant therapy [24,25]. Despite the use of aggressive therapy, only modest improvement in overall survival is noted over the last few decades with a 5-year overall survival rate of approximately 20-30% [26].…”
Section: Discussionmentioning
confidence: 99%